Firm-Level Technology Adoption in the State of Ceara in Brazil - Cirera, Xavier (World Bank, Washington, DC, 2021)
This paper uses a novel approach to measure technology adoption at the firm level and applies it to a representative sample of firms in the state of Ceará in Brazil. The paper develops a new measure of technology adoption at the firm level, which identifies the purpose for which technologies are used and the intensive and extensive uses. The survey allows for establishing several new stylized facts for Ceará. First, most firms still rely on pre-digital technologies to perform general business functions, such as business administration, marketing, sales and payments, or quality control. Second, these technology gaps are larger in smaller firms, in the manufacturing sector, with large gaps when it comes to Industry 3.0 and digitalization, and especially large in Industry 4.0 technologies. The paper also presents some evidence that the main challenge to accelerate technology adoption is lack of firm capabilities. Despite the availability of technology extension services in the state, firms are still unaware of the availability of support and unwilling to upgrade technologies.